STUDY ZN RECYCLING PROCESS FROM A PAINT FACTORY WASTE MATERIAL BY HYDROMETALLURGICAL ROUTE - LAKSANA ACHMAD , TRIA
Zinc is the fourth most-required metal in the world today after iron, aluminum, and copper. Zinc is used for the galvanization process (50 %), producing die-casting (20%) and copper alloys (12 %), zinc oxide (9 %), zinc dust (2 %), etc. These cause continuously increase the demand of zinc metal. Consequently the world zinc production must also increase continuously. Zinc ore conservation might can be carried out by zinc recycling from zinc-containing waste material such as paint factory waste material. The recycling process could be done either by pyrometallurgy or hydrometallurgy process. Hydrometallurgical route (oxidation roasting ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â– leaching ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â– purification) is considered as suitable process for extraction zinc from paint factory waste available. A series of leaching experiment has been done on calcine sample from paint factory waste material containing high zinc in order to study kinetic behavior of ZnO dissolution in sulfuric acid solution at constant temperature (room temperature, 60 0C and 80 0C). The concentration of sulfuric acid in solution during the test is relative constant. Three test solutions were used, these are ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â± 95 gr/l, ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â± 18,5 gr/l without initial Zn concentration and ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â± 18,5 gr/l with initial Zn concentration of 120 gr/l respectively. From the relationship between percent extraction and time that are obtained during leaching experiment, it is determined the step which controls ZnO dissolution process and it is also used for determining the activation energy of the process. The dissolution process can be controlled either by the rate of reaction at the interface or the rate of diffusion through diffusion layer. The purification process is initiated by pH adjustment (pH = 4) followed by KMnO4 addition. Further purification has been done by cementation process using zinc powder at room temperature, 60 0C and 80 0C for 30 and 60 minutes precipitation. Experiment results have exhibited that the leaching process of calcine in sulfuric acid solution is controlled by reaction rate at the interface between solid ZnO and liquid. The calculation results of activation energy of leaching experiment in high sulfuric acid concentration (98 gpl), and those in low sulfuric acid concentration (20 gpl), and low sulfuric acid concentration (20 gr/l) containing 120 gr/l Zn as initial concentration, are respectively 0,42 ; 0,47 ; 0,88 kkal /mol. The highest result obtained from the purification experiment which is conducted at temperature 80 0C for 1 hour is 97,83 %.